METHODS AND PRINCIPLES OF INFORMATION SECURITY IN DIGITAL TECHNOLOGIES - Bobobekova Хulkar Rasulberdiyevna; Radjabova Mashhura Rustamovna (American Journals Publishing, 2023)
The concept of "information" is used very widely today. A large amount of information literally overwhelms people. Scientific knowledge, for example, according to experts, increases by 2 times every five years. Information has consumer qualities, as well as its owners. It is very important for the owner to keep secret commercially important information that allows him to successfully compete in the production market. This requires certain actions aimed at protecting confidential information.
Keywords: Information security, security threat, information threat, espionage, cryptography, unauthorized access, risk, vulnerability.